Accountability in Autonomous Automobile Accidents: The Issue of Liability with Self-Driving Cars - Murphy, Joseph (Bellarmine Law Society Review, 2024)
With the increased implementation of self-driving cars on public roads, crashes and deaths caused by these vehicles have highlighted the complex matter of liability in these circumstances. The discussion of trials and cases surrounding deaths by autonomous vehicles illuminates how responsibility is deferred from the car manufacturer and placed primarily on the human behind the wheel. This paper highlights misconceptions about the level of automation in autonomous vehicles by the public and describes the necessity of proper tort liability law to adapt to the ever-changing automobile environment.